(untitled) (Journal of NELTA Karnali, 2024)
Reading comprehension is a fundamental skill necessary for academic success, yet its assessment and improvement, particularly in special education contexts, are often neglected. This study aims to investigate the reading comprehension abilities of deaf students (DS) compared to their non-deaf counterparts (NDS) in both seen (SRT) and unseen (URT) English reading texts. Employing a descriptive quantitative research design, reading comprehension tests were administered to eighty basic-level students, comprising forty DS and forty NDS from schools in Surkhet district, Nepal, selected through purposive sampling. The analysis revealed that NDS demonstrated higher reading comprehension abilities compared to DS in both SRT and URT. Additionally, male students outperformed female students overall, with both male and female NDS exhibiting superior performance to their DS counterparts. Moreover, students from both groups performed better in SRT than in URT, and NDS consistently outperformed DS in both types of texts. These findings underscore the challenges faced by DS in mastering reading comprehension skills and highlight the need for targeted interventions to enhance their literacy outcomes. The study contributes to the understanding of reading comprehension disparities between DS and NDS, informing educators and policymakers about the specific needs of deaf students in English language learning contexts.